2005
DOI: 10.1029/2005gb002546
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the satellite‐derived seasonal cycles of phytoplankton biomass and aerosol optical depth in the Southern Ocean: Evidence for the influence of sea ice

Abstract: [1] The relationship between the production of dimethylsulfide (DMS) in the upper ocean and atmospheric sulfate aerosols has been confirmed through local shipboard measurements, and global modeling studies alike. In order to examine whether such a connection may be recoverable in the satellite record, we have analyzed the correlation between mean surface chlorophyll (CHL) and aerosol optical depth (AOD) in the Southern Ocean, where the marine atmosphere is relatively remote from anthropogenic and continental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 58 publications
7
72
1
Order By: Relevance
“…MSA is thought to be a more or less conservative marker for DMS and lower MSA correlates with a lower extent of sea ice, because waters covered by sea ice in winter tend to be highly biologically active after sea ice melt, and a major source of DMS and hence MSA. [90,91] Satellite observations have shown that since 1950 the extent of the sea ice has diminished, corresponding to a decrease in MSA in the ice core, [90] which could imply a reduction in DMS emissions. [91,92] The modelling study of Sarmiento et al [93] suggests that as surface temperatures increase with increasing carbon dioxide, there will be an increase in primary productivity of between 0.7 and 8.1%.…”
Section: Feedbacksmentioning
confidence: 99%
See 1 more Smart Citation
“…MSA is thought to be a more or less conservative marker for DMS and lower MSA correlates with a lower extent of sea ice, because waters covered by sea ice in winter tend to be highly biologically active after sea ice melt, and a major source of DMS and hence MSA. [90,91] Satellite observations have shown that since 1950 the extent of the sea ice has diminished, corresponding to a decrease in MSA in the ice core, [90] which could imply a reduction in DMS emissions. [91,92] The modelling study of Sarmiento et al [93] suggests that as surface temperatures increase with increasing carbon dioxide, there will be an increase in primary productivity of between 0.7 and 8.1%.…”
Section: Feedbacksmentioning
confidence: 99%
“…[90,91] Satellite observations have shown that since 1950 the extent of the sea ice has diminished, corresponding to a decrease in MSA in the ice core, [90] which could imply a reduction in DMS emissions. [91,92] The modelling study of Sarmiento et al [93] suggests that as surface temperatures increase with increasing carbon dioxide, there will be an increase in primary productivity of between 0.7 and 8.1%. However, there would be major shifts from currently productive regions to other ocean regions.…”
Section: Feedbacksmentioning
confidence: 99%
“…Nevertheless, there is some observational evidence of considerable particle nucleation within the MBL in regions with enhanced DMS flux (Davison et al, 1996;O'Dowd et al, 1997;Clarke et al, 1998). In this context, the Southern Ocean surrounding the Antarctic continent shows striking biological activity during polar spring and summer (Gabric et al, 2005;Korhonen et al, 2008;Lana et al, 2011), provoking pronounced formation of biogenic sulfur aerosol (Minikin et al, 1998;Preunkert et al, 2007). Accordingly, nucleation events have also been reported from coastal Syowa (Ito, 1993) and the rather coastal Finnish Antarctic station Aboa (73 • 03 S, 13 • 25 W, 130 km away from coastline; Koponen et al, 2003), while at continental South Pole comparable events had to be typically associated with the impact local pollution during calm weather conditions (Park et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research seldom applies chlorophyll-a profiles and integrated chlorophyll-a signals to compare in situ and satellite match-ups. Current reports have already shown the obvious underestimation from satellite algorithms [6][7][8][9][10][11]. If considering the deep chlorophyll-a maximum and chlorophyll-a profile, there is a larger underestimation in SO chlorophyll-a retrieval.…”
Section: Errors For Fluorescence Approach Estimating Chlorophyll-amentioning
confidence: 99%
“…As a result, satellite measurements from space still have large errors in estimating phytoplankton biomass [4,5] and global chlorophyll-a satellite algorithms typically underestimate chlorophyll-a in the Southern Ocean [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%